Rising PSA during Testosterone Replacement Therapy - Gore, John (MedReviews, LLC, 2004)
Although testosterone replacement therapy (TRT) is indicated for the management of symptomatic hypogonadism, there is still controversy over whether TRT should be administered to middle-aged men for the clinical manifestations of andropause, regardless of whether the serum testosterone levels are depressed or not. Side effects of TRT may include fluid retention, gynecomastia, polycythemia, and exacerbation of existing prostate cancer. As a result, patients on TRT require meticulous surveillance including regular digital rectal examination and serum prostate-specific antigen (PSA) testing. Herein, we present the case of a middle-aged man with andropause and a rising PSA on TRT.